Characterization and comparison of mitogenomes of three 'eyed' turtles Sacalia spp. Issue 3 (2nd July 2020) - Lin, Liu; Chen, Huaiqing; Wang, Zhao; Gaillard, Daniel; Zhai, Xiaofei; Shi, Haitao
Abstract: In this paper, we characterized the mitogenomes of three 'eyed' turtles, the Beal's Eyed turtle ( Sacalia bealei ), the Four Eye-spotted turtle ( S. quadriocellata ), and the Hainan Four Eye-spotted turtle which was a unique lineage in the four-eyed turtle and considered as an independent species S. insulensis recently. The full lengths of the S. bealei and S. quadriocellata mitogenomes are 16, 564 bp, and 16, 555 bp, respectively, while the length of partial mitochondrial genome of S. insulensis is 16, 433 bp without tailed part of D-loop. All the genes exhibit the typical mitochondrial gene arrangement and transcribing directions of turtles. Phylogenetic analysis indicating that a deep divergence about 7.8% p distance was found between S. bealei and ( S. quadriocellata + S. insulensis ), and the divergence (2.8% in patristic distance) between S. quadriocellata and S. insulensis is comparable with other closely related species in turtles.